FULFILLMENT OF THE RIGHTS OF DOMESTIC VIOLENCE VICTIMS THROUGH RESTORATIVE JUSTICE POLICY - Dwi Rahmawati (Universitas Labuhanbatu, 2025)
Domestic violence remains a significant issue despite the enactment of Law Number 23 of 2004. The prevailing retributive approach is insufficient to provide comprehensive protection for victims, who are predominantly women. This study aims to examine the restorative justice policy in fulfilling the rights of DV victims and evaluate its effectiveness under Indonesian legal frameworks. Using a normative legal research method with statutory and literature approaches, this study investigates the potential application of restorative justice. The findings reveal that restorative justice offers a more humane approach by facilitating reconciliation between victims and perpetrators while promoting the recovery of victims' losses. However, its implementation faces challenges, including limited understanding among from law enforcement officials and the need for qualified mediators. Therefore, mediator training and socialization to the community and law enforcement are needed to ensure the successful implementation of restorative justice. Keywords: Violence; Domestic; Restorative Justice; Victims' Rights